Processing Time and Cognitive Effort of Longhand Note Taking When Reading and Summarizing a Structured or Linear Text. (April 2017) - Olive, Thierry; Barbier, Marie-Laure
We examined longhand note taking strategies when reading and summarizing a source text that was formatted with bullets or that was presented in a single paragraph. We analyzed cognitive effort when reading the source text, when jotting notes, when reading the notes, and when composing the summary, as well as time spent in these activities and the content of the notes and the summaries. With a formatted text, students' perceived comprehension difficulty was lower and they expended less cognitive effort, spent less time reading the text, and noted more ideas. While composing the summary, only those students who read the formatted source text continued selecting ideas in their notes. Finally, the summaries were unaffected by the formatting of the source text. The study shows that formatting a source text with bullets facilitates note taking by helping students to grasp its structure and by reducing the cognitive effort of reading.